Outcomes of mild-to-moderate postresuscitation shock after non-shockable cardiac arrest and association with temperature management: a post hoc analysis of HYPERION trial data - Ines Ziriat; Aurélie Le Thuaut; Gwenhael Colin; Hamid Merdji; Guillaume Grillet; Patrick Girardie; Bertrand Souweine; Pierre-François Dequin; Thierry Boulain; Jean-Pierre Frat; Pierre Asfar; Bruno Francois; et al. (Annals of Intensive Care, 2022)
Abstract Background Outcomes of postresuscitation shock after cardiac arrest can be affected by targeted temperature management (TTM). A post hoc analysis of the “TTM1 trial” suggested higher mortality with hypothermia at 33 °C. We performed a post hoc analysis of HYPERION trial data to assess potential associations linking postresuscitation shock after non-shockable cardiac arrest to hypothermia at 33 °C on favourable functional outcome. Methods We divided the patients into groups with vs. without postresuscitation (defined as the need for vasoactive drugs) shock then assessed the proportion of patients with a favourable functional outcome (day-90 Cerebral Performance Category [CPC] 1 or 2) after hypothermia (33 °C) vs. controlled normothermia (37 °C) in each group. Patients with norepinephrine or epinephrine > 1 µg/kg/min were not included. Results Of the 581 patients included in 25 ICUs in France and who did not withdraw consent, 339 had a postresuscitation shock and 242 did not. In the postresuscitation-shock group, 159 received hypothermia, including 14 with a day-90 CPC of 1–2, and 180 normothermia, including 10 with a day-90 CPC of 1–2 (8.81% vs. 5.56%, respectively; P = 0.24). After adjustment, the proportion of patients with CPC 1–2 also did not differ significantly between the hypothermia and normothermia groups (adjusted hazards ratio, 1.99; 95% confidence interval, 0.72–5.50; P = 0.18). Day-90 mortality was comparable in these two groups (83% vs. 86%, respectively; P = 0.43). Conclusions After non-shockable cardiac arrest, mild-to-moderate postresuscitation shock at intensive-care-unit admission did not seem associated with day-90 functional outcome or survival. Therapeutic hypothermia at 33 °C was not associated with worse outcomes compared to controlled normothermia in patients with postresuscitation shock. Trial registration ClinicalTrials.gov, NCT01994772